Impact of the Spittlebug Mahanarva spectabilis on Signal Grass - Tiago Teixeira Resende; Alexander Machado Auad; Marcy das Graças Fonseca; Thiago Henrique dos Santos; Tamiris Moreira Vieira (The Scientific World Journal)
The aim of this study was to determine the damage in Brachiaria ruziziensis (Germain & Edvard) according to the density of and exposure time to adults of Mahanarva spectabilis (Distant, 1909) (Hemiptera:Cercopidae). Each plant was kept with 0, 12, 18, or 24 adults of M. spectabilis for five or ten days. Then, the insects were removed from the plant, and the following parameters were evaluated: content and loss of chlorophyll, visual damage score, shoot dry mass, and the capability for regrowth. In fact, plants exposed to the highest level of infestation for 10 days showed an 80.97% loss of chlorophyll, which is 25% higher than that shown by the plants exposed for five days. The damage score also increased with infestation levels. In the levels of 12 and 18 adults per plant, the damage score increased with increasing time of exposure. The dry mass content was higher in plants exposed to 24 insects for 10 days, suggesting that the attack of spittlebugs caused premature drying of the plant. These effects caused significant reduction in the number of tillers of infested plants. Our results indicate that exposure to adults of M. spectabilis causes significant damage and affects the development and persistence of B. ruziziensis plants.